Perceptions of the National Credit Regulator on the usefulness of the debt counselling process in South Africa - Masilo, K. H. (Journal of Economics and Behavioral Studies, 2018)
The South African National Credit Regulator is responsible for the regulation of credit industry, registration and training of debt counsellors, enforcement and monitoring compliance of the provisions of the National Credit Act. The aim of this paper is therefore to analyse the perceptions of the National Credit Regulator on the usefulness of debt counselling process in South Africa. A qualitative approach, which was exploratory in nature, was adopted for this study. Ten employees from the National Credit Regulator’s office were interviewed. There was no evidence that debt counsellors were managing the debt counselling service effectively. It was also observed that the debt counsellors received insufficient support from the National Credit Regulator. The paper recommends that the National Credit Regulator should adequately support the debt counsellors so that they can effectively manage debt counselling service and ultimately assist the overindebted consumers. Debt counsellors training curriculum should also be outcomes- based approach with exposure to business management.